The Influence of Gadgets on Early Childhood Social Development in Hidayatullah Islamic Kindergarten School Semarang - Munawar, Muniroh; Zuhri, Putri RA (Indonesian Journal of Early Childhood Education Studies, 2018)
This study aims to determine the effect of using gadgets on social development of early childhood. This type of research is quantitative research. The population in this study was students of Group A of Hidayatullah Islamic Kindergarten School Semarang academic year 2017/2018. The samples taken were 32 students of Hidayatullah Islamic Kindergarten School Semarang by using purposive sampling technique. Data in this research was obtained through questionnaire.The results of the questionnaire analysis obtained t count> t table (5.063> 2.042) with p = 0,000. The result of this study indicates that there is a significant influence of the use of gadgets on social development of early childhood, that is the use of gadgets brings negative impacts because children prefer to use gadgets, so the hypothesis proposed accepted. Based on the results of the study, it is also known that 46.1% early childhood social development in Hidayatullah Islamic Kindergarten School Semarang is influenced by the use of gadgets.